CT Findings, Radiologic-Pathologic Correlation, and Imaging Predictors of Survival for Patients With Interstitial Pneumonia With Autoimmune Features. - Chung, Jonathan H. (AJR Am J Roentgenol, 2017)
OBJECTIVE: To determine the CT findings and pattern in interstitial pneumonia with autoimmune features (IPAF) and to assess whether imaging can predict survival in IPAF. MATERIALS AND METHODS: This retrospective study was HIPAA compliant and approved by our institutional review board. We included 136 subjects who met criteria for IPAF and had diagnostic quality chest CT scans from 2006 to 2015; 74 of these subjects had pathology available for review within one year of chest CT. CT findings and usual interstitial pneumonitis (UIP) pattern of disease were assessed as was the pattern of UIP on pathology. Analysis of chest CT findings associated with survival was performed using standard univariate and multivariable Cox proportional hazards methodology as well as the unadjusted log rank test; survival was presented visually using the Kaplan-Meier survival curve estimator. RESULTS: The majority of IPAF subjects had a high confidence UIP pattern on CT (57.4%, 78/136). A substantial minority of subjects had an inconsistent with UIP pattern on CT (28.7%, 39/136). A UIP pattern on CT was associated with smoking (<p-value 0.01), male sex (<p-value 0.01), and older age (p-value <0.001). Approximately, ¼ of subjects had a nonspecific interstitial pneumonitis pattern on CT. Interestingly, nearly a tenth of subjects had a CT pattern most consistent with hypersensitivity pneumonitis rather than customary CT patterns ascribed to lung disease from connective tissue disease. Most subjects with a possible UIP pattern on CT had UIP on pathology (83.3%). Focused multivariate analysis demonstrated that honeycombing (HR 2.17, 95% CI 1.05–4.47) and pulmonary artery (PA) enlargement (HR 2.08, 95% CI 1.02–4.20) on CT were independent predictors of survival. CONCLUSIONS: IPAF most often presents with a UIP pattern on CT and is associated with worse survival when there is concomitant honeycombing or PA enlargement.